Fabrication of CB/Ni3S2 micro-nanostructure decorated foam with Janus wettability towards solar-driven interfacial evaporation - Yin, Xiaoli; Yin, Tianyu; Li, Peiyuan; Yu, Sirong; Lu, Zehang (Journal of environmental chemical engineering, 2025)
The ever-increasing population and environmental pollution have led to a global crisis of freshwater scarcity. Solar-driven interfacial evaporation, as an eco-friendly and cost-effective solution, holds great promise to address this issue. In this work, the solvothermal reaction and spray coating were adopted to fabricate Janus Carbon black-Polydimethylsiloxane-Heazlewoodite-Nickel foam (CB-PDMS-Ni3S2-NF), a material that integrated asymmetric wettability and intense solar absorption property for efficient interfacial evaporation. CB-PDMS-Ni3S2-NF displayed superhydrophobicity on one side and hydrophilicity on the other. When exposed to solar irradiation, the surface temperature would rise sharply. Eventually, CB-PDMS-Ni3S2-NF presented an evaporation rate of 1.47 kg·m−2·h−1 and evaporation efficiency of 92.05 %, respectively, under 1-sun irradiation. In addition, it could maintain a high evaporation rate even when floating in solutions containing 5 M sodium chloride (NaCl) or methylene blue. Importantly, the stable CB-PDMS-Ni3S2-NF was able to endure multiple mechanical tests and effective against the accumulation of salt or contaminants. Moreover, it could be manipulated and recycled easily owing to its fast magnetic responsiveness. This work is believed that provides a promising material for efficient interfacial evaporation. •A foam exhibiting Janus wettability and intense solar absorption is presented.•The foam as an interfacial evaporator shows high evaporation rate and efficiency.•The foam can endure multiple mechanical tests and resist the salt accumulation.•The foam can be easily manipulated and recycled with the aid of magnetic field.